Perancangan Konten Digital dan Pelatihan Pemanfaatan Marketplace sebagai Sarana Promosi Kerajinan Tenun Leny Bumpak - Ardesta, Pauta Sapa; Saputri, Arnila; Peranata, Suria; Zaki, Khozin; Indra, Yetti Afrida (Yayasan Daarul Huda Kruengmane, 2025)
Leny Bumpak woven crafts are a local cultural heritage from Seluma Regency, Bengkulu, known for their high historical and aesthetic value. However, limitations in promotional strategies and marketing have resulted in low public awareness of these traditional products, especially in today's digital era. This community service project aims to design digital content and provide training for weavers in utilizing marketplaces and social media as tools for promotion and market expansion.The methods used include observation, interviews, hands-on training, and assistance in operating platforms such as Shopee and TikTok. The results show that artisans successfully improved their skills in creating engaging visual content, managing online stores, and actively promoting their products through social media. Digital content utilization proved effective in increasing audience engagement and enhancing product competitiveness in the national market.Through this training, it is expected that the artisans will be able to preserve local cultural values while adapting to technological advancements, thus supporting the sustainability of traditional weaving businesses.